(untitled) (World Economics and Finance Bulletin, 2024)
This article delves into the intricate landscape of technical systems management within the dynamic framework of the digital economy. As technology rapidly evolves, organizations encounter a spectrum of challenges in maintaining and optimizing their technical infrastructure. From cybersecurity threats to the complexities of integrating emerging technologies, the problems are manifold. Simultaneously, the digital economy offers unprecedented prospects, such as enhanced efficiency, innovation, and global connectivity. This article explores the dual nature of this landscape, dissecting the problems faced by businesses in managing technical systems while highlighting the promising prospects that emerge in the digital transformation journey. By understanding these challenges and opportunities, organizations can navigate the digital terrain with strategic foresight, ensuring resilient and adaptive technical systems management in the ever-evolving digital economy.